ANALISIS PATOLOGI SOSIAL GENERASI MUDA DALAM PELAKSANAAN SYARIAT ISLAM DI KABUPATEN ACEH BARAT - Nellis Mardhiah (Jurnal Public Policy, 2015)
Social pathology is a social disease suffered by young people today are happening in the land of shari’a. The type of social pathology that is mixing young people who have the freedom, do not appreciate the values and norms, and attitudes of young people who are far from the religious values in the code of conduct rules of Islamic law in Aceh Barat district based on the rule of law. This is a consequence of globalization is a world without borders, so that globalization also transfused to the westernization of Islamic youth in today's world. With the westernization of today's young generation to generation, the social pathology easily occur. The authors of this research focuses on the West Aceh district as a district known as the Islamic Shari'a. This study used a qualitative descriptive analysis methodologies for being able to respond to the social pathology that is happening today. The purpose of this paper is to contribute to the West Aceh district government in enforcing Islamic law in the Islamic Shari'a, which was valid as the rule of law to enforce strict Islamic law. The results showed enforcement of Islamic law in Aceh Barat district special because the younger generation is often weak and apathetic to the rules of Islamic law until the reign of West Aceh Regent reiterated in Rule Number 5 of 2010 on the Enforcement of Islamic Law in Aceh Barat district in the application of Islamic dress in Regency West Aceh.Keywords: Social Pathology, Youths, Islam.